Dance - Grau, Andrée (New York Dorling Kindersley, 2000)
Surveys all forms of dance throughout the world, discussing its cultural and social significance, costume, history, and noted dancers and choreographers.
Keywords: Dance -- Juvenile literature; Dance -- Cross-cultural studies -- Juvenile literature; Folk dancing -- Juvenile literature